Transurethral Retrograde Fishing the Double J Urethral Stent: A Tertiary Children Hospital's Experience With a New Technical Strategy - Yu, Chengjun; Wei, Chun; Dong, Junjun; He, Xingyue; Wei, Yi; Wen, Sheng; Lin, Tao; He, Dawei; Wu, Shengde; Wei, Guanghui (Frontiers in Pediatrics, 2022)
Purpose: To provide a new strategy for non-cystoscopic double J urethral stent (JJS) removal, the transurethral retrograde fishing the double J urethral stent (TURFJJS), that avoids general anesthesia in pediatric populations. Methods: We retrospectively reviewed the JJS removal records of patients having ureteropelvic junction obstruction (UPJO). We analyzed differences in success-removal rates, operation-related severe complications, total cost, duration, and parental satisfaction between TURFJJS and traditional cystoscopic double J urethral stent removal (CJJSR) procedures. Results: A total of 324 UPJO patients were included in this study. CJJSR yielded a success rate of 100%. TURFJJS achieved a success rate of 94.3%. The TURFJJS was just an outpatient procedure and the total cost of it was about 800 Chinese yuan (124 united states dollars). There were no severe JJS removal-related complications using TURFJJS. Parental satisfaction was 98.2% and 92.5% for the CJJSR and TURFJJS protocols, respectively. Conclusion: TURFJJS is safe, effective, cost-effective, and well tolerated in pediatric patients, minimizing or eliminating the need for general anesthesia, additional hospitalization, and waste of time. TURFJJS should be widely used in pediatric urology.